Analisis implementasi kebijakan penanganan pandemi Covid-19 di Selandia Baru - Reza Fajar Raynaldi (Jurnal Administrasi dan Kebijakan Publik, 2021)
Covid-19 as a pandemic phenomenon has been impacting global life since last year. Almost all countries in the world encounter crises in various sectors. One of the countries that succeeded in handling the Covid-19 cases is New Zealand. The success attracted many researchers to conduct a research to analyze the New Zealand Government's moves in handling the pandemic to take a lesson from it. Moreover, the pandemic is still not over yet. This research focuses on the public policy dimension from the government of New Zealand to handle the pandemic and has an objective to analyze the factors that contribute to the effectiveness of policy implementation from the government of New Zealand, using the policy implementation model from George C. Edwards. This research uses a qualitative method with a desk study as a means for collecting data. The result of this research is clear communication, adequate resources, and slight disposition are the factors that contribute to the success and effectiveness of policy implementation in New Zealand in order to handle the Covid-19 pandemic. However, the bureaucracy structure factor with the fragmentation of health institutions between national and local governments might have undermined that success.